The relationship between religious practice and depression among community-dwelling older people - Che Hasan, Muhammad Kamil; Jaafar, Siti Nur Illiani; Zakaria, Siti Suhana; Abd Rashid, Nor'ain; Rosli, Che Radhiatul Asyikin; Piriyasart, Jitlada (Universiti Putra Malaysia, 2025)
Introduction: Research has found that there is a need among older people to have strong motivational religiosity to help combat the impact of depression they face later in life. Thus, religious practices among the older generation are warranted to reduce depression. This study aims to identify the association between religious practices among the older people living in community-dwellings and depression. Methods: A survey was conducted using a Malay version of Geriatric Depression Scale (GDS) and the Duke University Religion Index (DUREL-M) in a selected district in Kuala Terengganu. The sociodemographic of the older people, religious practices and depression were analysed using descriptive statistics, while the Pearson’s correlation coefficient was used to investigate the relationship between religiosity and depression. Results: There were 24.5% out of 240 older people that had depression. A total of 54% of older people attended religious practices while 74% of them performed religious activities by themselves, while the majority of them (97.5%) claimed to have strong faith and motivation towards their religion. Moreover, there were significant relationships between attending religious practices, performing religious activities, having strong faith and motivation towards religion and depression among older people living in community-dwellings. Conclusion: The findings suggest that religiosity may lower the risk of depression, as indicated by the negative correlation observed. Therefore, religious engagement could be a potential strategy for mental health practitioners, caregivers, and policymakers to support the psychological well-being of the older generation.